Tiny thoughts on shyness - Bezenac, Agnes; Bezenac, Salem (Beirut Dar al Maaref bookshop, 2020)
Greeting people is difficult for Bonzo, a well-humored encounter helps him to realize that greeting others is not so hard after all
Education
1
Keywords: Educational psychology